Colombia y Venezuela: dos orilla opuestas de la aldea global en la era - caída del muro de Berlín (2011)
In the decades after the fall of the Berlin Wall, when the concept of globalization of the economy was generalized, most international relations scholars approached the subject from the assumption of a relative unification on the principles that regulate the world system in pursuit of common objectives. However, in the political-economic scenario contradictions and current arrangements are overlapped doing more and more distant the idea of the Global Village. Thus, the primary objective of this paper is to analyze the differences in foreign policy of Colombia and Venezuela over the past decades, and to inquire about the ideological assumptions that support them, prior to the formulation of a research project which seeks to assess the impact of this policy on economic relations between two countries.